2016
DOI: 10.1016/j.amsu.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cervical esophagotomy for foreign body extraction - Case report and comprehensive review of the literature

Abstract: IntroductionEsophageal foreign bodies are an important and serious cause of morbidity and mortality in both children and adults. Due to the possibility of serious complications, i.e. perforation, necrosis, mediastinitis, and fistulation, rapid and accurate diagnostic measures with subsequent therapy are necessary.Case reportWe are reporting a case of a 55-year-old, mentally impaired patient that has swallowed a foreign body, which subsequently became lodged in his esophagus. Due to the fact that endoscopic rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A foreign body impacted in the esophagus requires immediate attention and early removal, because it may cause perforation, mediastinitis, and respiratory distress depending on the nature of the objects. 3,4 In this case, the foreign body could not cross the lower esophageal sphincter and had impacted in the esophagus causing dysphagia. Why the eye ball got trapped at expandable lower part is still unclear but the only possible explanation would be that the raw muscle, as well as the sphincter of the lower of esophagus must have swollen in transit, forcing the eye to become wedged.…”
Section: Discussionmentioning
confidence: 90%
“…A foreign body impacted in the esophagus requires immediate attention and early removal, because it may cause perforation, mediastinitis, and respiratory distress depending on the nature of the objects. 3,4 In this case, the foreign body could not cross the lower esophageal sphincter and had impacted in the esophagus causing dysphagia. Why the eye ball got trapped at expandable lower part is still unclear but the only possible explanation would be that the raw muscle, as well as the sphincter of the lower of esophagus must have swollen in transit, forcing the eye to become wedged.…”
Section: Discussionmentioning
confidence: 90%
“…There are several types of endoscopic tools used to extract foreign bodies and the tool of choice depends on the characteristics of the foreign body. More commonly used tools include rat tooth forceps, alligator forceps, retrieval nets, protector hoods, and overtubes [ 6 , 7 ]. These last two tools are indicated in the removal of sharp objects.…”
Section: Discussionmentioning
confidence: 99%
“…In roughly 80% of cases of all foreign body ingestion, the object will pass spontaneously through the GI tract. However, in the remaining 20% of cases, retrieval of foreign bodies via esophagogastroduodenoscopy (EGD) is indicated in order to avoid serious complications, which can include perforation, necrosis, retropharyngeal abscess, mediastinitis, and fistulization [ 2 , 3 , 7 ]. Endoscopic removal of foreign bodies has a high success rate and low complication rates [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 80–90% of all foreign bodies trapped in the esophagus pass spontaneously whereas the remaining 10–20% of cases will require an endoscopic intervention to remove the FBI [3]. …”
Section: Introductionmentioning
confidence: 99%